The Use of Soft System Methodology in Evaluating the Business Strategies in Organic Farming: The Case from Yogyakarta, Indonesia - Prasetyaningtyas, Sekar Wulan; Maarif, Syamsul; Sobir, Ridwani; Hermawan, Aji (AIBPM Publisher, 2019)
The purpose of this research was to evaluate the business strategies applied in one of the sustainable organic farming in Yogyakarta, Indonesia. The methodology used is Soft System Methodology (SSM). SSM is an organizational process modeling method that can be used for general problem resolution and change management. Rich picture, Root definitions and conceptual model were presented in the paper. Data were taken using focus group discussion and in-depth interviews with the owner, staffs, and farmers from the organic farm. The focus of this research is to get knowledge about the actors, their behavior, relationships and their influence on decision - making processes. From the analysis, eight main results were obtained as the key strategies in organic farming: identification of actors and critical factors in the farm, vision and mission socialization, operational evaluation, transformation, managerial improvement, measurement of revenue and profit, consistency in sustainability indicator used, and mitigation plan.